ChemInform Abstract: Flower‐Like Cu2In2ZnS5 Nanosheets: A Novel Promising Photoelectrode for Water Splitting. Issue 28 (June 2016) - Hong, Tiantian; Liu, Zhifeng; Zhang, Jing; Li, Guangmin; Liu, Junqi; Zhang, Xueqi; Lin, Shaohua
Abstract: A flower‐like Cu2 In2 ZnS5 structure composed of nanosheets on an indium tin oxide (ITO) substrate is hydrothermally synthesized from a mixture of CuCl, InCl4, Zn(OAc)2, and thioacetamide in EtOH together with the ITO substrate (autoclave, 200 °C, 1 h).